Influence of Parameter on Dynamic Load and Load Sharing Characteristic of Split Torque-combine Power Gear Transmission System - He Lin; Sanmin Wang (Jixie chuandong)
For the improvements of dynamical load stability of split torque-combine gear transmission， dynamical models of the system consisting of spur gears and herringbone gears is set up including excitations of multiple backlashes. The Gaussian elimination technique is introduced to deal with the elimination of extra rigid body displacements， ultimately， the dynamics equations are reduced to be 9 degrees of freedom. By applying the fourth order Runge-Kutta algorithm to solve the system dimensionless dynamical equations， dynamic load characteristic is analyzed under the excitations of backlash， general transmission error and time-varying mesh stiffness. The results show that dynamic load factor happens to jump to 2.705 under the backlash excitation， load sharing characteristic keeps very similar on the same stage when general transmission error varies， the dynamic characteristic vibrates severely on split torque gears while the perturbation factor of time-varying mesh stiffness is larger than 0.25， the investigation will provide a guidance for dynamic load design of this typical gear system.